Quest from Disability to Ultimate Ability through Sexuality: A Study of the Movie Margarita with a Straw - Bijender Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper is an attempt to investigate the treatment of an urge to lead an everyday life and sexuality of a woman with a disability in society across nationalities. Disabled people often are neglected at different stages in their life by other people. The movement for the rights of disabled persons has impacted the community in general and governments in particular, owing to which governments have taken measures to improve their lives. However, social perception still stigmatises them and their desires across cultures. To examine a woman with disability’s zeal to lead an everyday life and her treatment by relatives and friends, this research selects Margarita with a Straw movie as a primary source for study. To accomplish the study, critical disability theory is used as a tool to analyse the chosen movie. The study proves that disabled persons are not only neglected physically but their urges and emotions, too. Loneliness furthers their disability. But, only a few among the persons with Disabilities, like the lead character in the movie selected, transcend the social disability and attain ultimate ability too.